Synthesis, characterization and apoptosis induction by cyanobacteria-derived neurotoxins: evaluating L-BMAA, 2,4-DAB, and AEG as potential anticancer agents against brain and breast cancer cells - Uthra, Chandrabose; Nagaraj, Karuppiah; Muralitharan, Gangatharan; Al-Ansari, Mysoon M.; Velmurugan, Gunasekaran (Chemical papers, 2025)
Cancer remains a significant global health challenge, with brain and breast cancers posing considerable obstacles due to their aggressive progression and limited therapeutic options. Exploring natural sources for novel treatments offers a promising avenue for combating these malignancies. Cyanobacteria, traditionally associated with harmful algal blooms, have gained attention for their bioactive compounds with potential therapeutic applications. This study investigates the anticancer potential of cyanobacteria-derived compounds, including L-BMAA, 2,4-DAB, and AEG. Commercially available L-BMAA and 2,4-DAB were utilized, while AEG was synthesized and confirmed via NMR spectroscopy. Cytotoxicity against brain (N2a) and breast cancer (MDA-MB-231) cell lines was evaluated using MTT and trypan blue exclusion assays, revealing significant cytotoxic effects, time-dependent apoptosis induction, and reduced cell viability. Fluorescence staining (AO/EtBr, DCFH-DA, Hoechst, FDA, and Rho-123) indicated increased ROS levels, mitochondrial damage, nuclear envelope disruption, and further reductions in viability. Protein expression analysis demonstrated that 2,4-DAB upregulated pro-apoptotic proteins Bax and caspase-8 while downregulating anti-apoptotic proteins BCL-2 and p-Akt, confirming apoptosis activation. The findings suggest that cyanobacteria-derived neurotoxins, including L-BMAA, 2,4-DAB, and AEG, act as initiators of apoptosis in N2a and MDA-MB-231 cells through modulating apoptotic and anti-apoptotic pathways, highlighting their potential as anticancer agents for brain and breast cancer therapy.
Gesehen am 20.01.2026